Analisis Karakter Agronomi dan Fisiologi Padi pada Kondisi Cekaman Rendaman Stagnan - Sujinah, Sujinah; Agustiani, Nurwulan; Rumanti, Indrastuti A. (Jurnal Penelitian Pertanian Tanaman Pangan, 2020)
Stagnant flooding is a condition in swampy area and become constraints which causes decrease yield of rice. Therefore, it is necesarry of varieties that have tolerance to stagnant flooding. The purpose of this research were to analyze of agronomic and physiological characters of rice on stagnant flooding stress. The experiment was conducted at two environmental conditions in wet season of 2017/2018 in Sukamandi Experimental Station, Subang, West Java. A total of 10 genotypes (IR14D157, IRRI 119, IRRI 154, IR14D121, Inpara 3, Inpara 4, Inpara 8, Inpari 30, Tapus, and IR 42) were planted use Randomized Complete Block Design (RCBD) with 4 replicants. Variables consisted of growth (plant height, tillering, green leaves), stem elongation, nonstructural carbohydrate, chloropyll content, stem aerenchyma, yield component, and yield. The result showed that stagnant flooding caused an increase in plant height of 4% , stem elongation, and flowering. In addition, it was observed the decreased of tiller number of 50%, nonstructural carbohydrate, chloropyll content, productive tiller, spikelet number, % filled grain, and yield. Genotype of IR14D121 and Tapus showed the highest productivity, of 4,91 t/ha and 4,45 t/ha at stagnant flooding, at which productivity decreased up to 20% compared to the optimum condition.